Potential utilities of mask‐wearing and instant hand hygiene for fighting SARS‐CoV‐2 - Ma, Qing‐Xia; Shan, Hu; Zhang, Hong‐Liang; Li, Gui‐Mei; Yang, Rui‐Mei; Chen, Ji‐Ming (Journal of medical virology, 2020)
The surge of patients in the pandemic of COVID‐19 caused by the novel coronavirus SARS‐CoV‐2 may overwhelm the medical systems of many countries. Mask‐wearing and handwashing can slow the spread of the virus, but currently, masks are in shortage in many countries, and timely handwashing is often impossible. In this study, the efficacy of three types of masks and instant hand wiping was evaluated using the avian influenza virus to mock the coronavirus. Virus quantification was performed using real‐time reverse transcription‐polymerase chain reaction. Previous studies on mask‐wearing were reviewed. The results showed that instant hand wiping using a wet towel soaked in water containing 1.00% soap powder, 0.05% active chlorine, or 0.25% active chlorine from sodium hypochlorite removed 98.36%, 96.62%, and 99.98% of the virus from hands, respectively. N95 masks, medical masks, and homemade masks made of four‐layer kitchen paper and one‐layer cloth could block 99.98%, 97.14%, and 95.15% of the virus in aerosols. Medical mask‐wearing which was supported by many studies was opposed by other studies possibly due to erroneous judgment. With these data, we propose the approach of mask‐wearing plus instant hand hygiene (MIH) to slow the exponential spread of the virus. This MIH approach has been supported by the experiences of seven countries in fighting against COVID‐19. Collectively, a simple approach to slow the exponential spread of SARS‐CoV‐2 was proposed with the support of experiments, literature review, and control experiences.